Transient receptor potential ankyrin 1 (TRPA1) plays a critical role in a mouse model of cancer pain. Issue 2 (30th October 2018) - Antoniazzi, Caren Tatiane De David; Nassini, Romina; Rigo, Flávia Karine; Milioli, Alessandra Marcon; Bellinaso, Fernando; Camponogara, Camila; Silva, Cássia Regina; de Almeida, Amanda Spring; Rossato, Mateus Fortes; De Logu, Francesco; Oliveira, Sara Marchesan; Cunha, Thiago Mattar; et al.
Abstract : There is a major, unmet need for the treatment of cancer pain, and new targets and medicines are required. The transient receptor potential ankyrin 1 (TRPA1), a cation channel expressed by nociceptors, is activated by oxidizing substances to mediate pain‐like responses in models of inflammatory and neuropathic pain. As cancer is known to increase oxidative stress, the role of TRPA1 was evaluated in a mouse model of cancer pain. Fourteen days after injection of B16‐F10 murine melanoma cells into the plantar region of the right hind paw, C57BL/6 mice exhibited mechanical and thermal allodynia and thigmotaxis behavior. While heat allodynia was partially reduced in TRP vanilloid 1 (TRPV1)‐deficient mice, thigmotaxis behavior and mechanical and cold allodynia were absent in TRPA1‐deficient mice. Deletion of TRPA1 or TRPV1 did not affect cancer growth. Intrathecal TRPA1 antisense oligonucleotides and two different TRPA1 antagonists (HC‐030031 or A967079) transiently attenuated thigmotaxis behavior and mechanical and cold allodynia. A TRPV1 antagonist (capsazepine) attenuated solely heat allodynia. NADPH oxidase activity and hydrogen peroxide levels were increased in hind paw skin 14 days after c ancer cell inoculation . The antioxidant, α‐lipoic acid, attenuated mechanical and cold allodynia and thigmotaxis behavior, but not heat allodynia. Whereas TRPV1, via an oxidative stress‐independent pathway, contributes partially to heat hypersensitivity, oxidative stress‐dependent activation of TRPA1 plays a key role in mediating thigmotaxis behavior and mechanical and cold allodynia in a cancer pain model. TRPA1 antagonists might be beneficial in the treatment of cancer pain. Abstract : What's new? While cancer is a frequent cause of pain, mechanisms underlying the association are poorly understood. Moreover, therapeutic options for cancer pain are limited, and affected patients are undertreated. Here, using a mouse model of cancer pain, the authors identify transient receptor potential ankyrin 1 (TRPA1), a cation channel expressed by pain receptors, as a primary transducer of cancer pain. In animals, TRPA1 deletion attenuated sensitivity to mechanical and cold pain stimuli. Similar effects were produced upon TRPA1 blockade via pharmacological inhibition and TRPA1‐targeted antisense oligonucleotides. The findings warrant further investigation of TRPA1 antagonism as a means of treating cancer pain.